The ACE Study I: Childhood Trauma and Adult Health. (Kanopy Streaming, 2015)
"I think of my training as a medical student; I learned nothing of this. I think every medical student should be taught about adverse childhood experiences, abuse, violence, and neurodevelopment, and how the consequences will lay hidden right in front of their eyes unless it's a standard part of medical care to inquire about it."- Robert Anda, MD This video, intended for general audiences and policymakers, discusses the ACE Study's origins, findings, and the consequences of adaptive behaviors. Topics Origins and design of the ACE Study Findings of the ACE Study Intergenerational transfer Obesity Addictions Depression Cost to society Raising children safely